Effects of substituting iron for aluminum on the low-temperature catalytic activity and sulfur resistance of hydrotalcite-derived LNT catalysts. (October 2022) - Lyu, Yu; Lyu, Gang; Li, Yunqing; Li, Bo; Chen, Ke; Song, Chonglin; Li, Zhenguo; Pan, Suozhu
Abstract: The storage and reduction of NOx on a series of Fe-modified hydrotalcite-based lean NOx trap catalysts were assessed, together with the product selectivity. The crystal structures and micromorphologies of these materials were characterized using X-ray diffraction and scanning electron microscopy, while in situ diffuse reflectance Fourier transform infrared spectroscopy was used to evaluate the evolution of transition state species. The introduction of Fe was found to improve the synergistic interaction between the Mg and Fe in the hydrotalcite structure, allowing these catalysts to work efficiently at low temperatures. In addition, both Pt/BaO/MgAlO and Pt/BaO/MgFeO catalysts exhibited better NOx adsorption and reduction performance compared with Pt/BaO/Al2 O3 . The superior performance of the former two materials was attributed to the enhanced adsorption of NOx in the form of nitrates and nitrites by Fe and Mg and to the ready decomposition of these nitrates at low temperatures. A Pt/BaO/MgFeO catalyst showed excellent low temperature activity and high selectivity for N2 together with superior sulfur resistance compared with Pt/BaO/Al2 O3 . Graphical abstract: Image 1 Highlights: This study prepared a series of hydrotalcite-derived lean NOx trap catalysts. The introduction of Fe was found to increase the NOx removal efficiency at low temperature because of improving the synergistic interaction between the Fe and Mg in the hydrotalcite structure. Pt/BaO/MgFeO has better sulfur resistance than traditional Pt/BaO/Al2 O3 catalysts.